Valve Plate Structural Optimal Design and Flow Field Analysis for the Aviation Bidirectional Three-Port Piston Pump - Dunhui Xiao (Energies, 2021)
This paper designed and optimized a bidirectional three-port valve plate structure for solving the matching problem of flow rate and pressure in the aerospace pump-controlled differential hydraulic cylinder. This design aims to make the valve plate work well under the bidirectional high-speed condition. The model was set up using dynamic mesh and sliding mesh, and the simulation is conducted by FLUENT. In addition, the flow field of inlet and outlet flow rate pulsations, pressure pulsation in cylinder, and non-dead-point transition zone of four cases are analyzed to optimize the valve plate in this work. The numerical results show that different angles of non-dead-point transition zones of the valve plate have a big impact on the performance of the piston pump. For example, the flow rate pulsation reaches the minimum when the angle of non-dead point transition zone is greater than or equal to the angle of a cylinder port. However, at this time, the closed compression would occur and the pressure inside the cylinder would rise rapidly as the piston moves to the non-dead point zone, thus resulting in serious pressure overshoot. In addition, if the angle of non-dead point transition zone is reduced within a certain range, the pressure overshoot will be reduced drastically, and the flow pulsation rate will rise a bit. The study suggests that it is necessary to adjust the angle of non-dead point transition zone to balance the pressure overshoot and flow pulsation of the pump to obtain the optimal kidney structure of the valve plate.